Gest??o de portf??lio no desenvolvimento de novos produtos no setor das telecomunica????es brasileiro: estudo de m??ltiplos casos - Frederico, Ang??lica (2016)
The growing dynamism and business changes in the telecommunications sector drive companies to hone the products on the market to meet the increasingly demanding consumers. In order to offer products successfully, companies need to select projects of development of new products (DNP) from a portfolio. The aim of this study is how to understand the portfolio management influences the development of new products in the Brazilian telecommunications operators, identifying the problems and DNP portfolio management models used, thus helping to raise the good practices in this sector. To achieve this goal, we designed a qualitative survey through multiple case study in fixed and mobile telephony Brazilian companies. Armed with the information collected during interviews in selected companies in the telecommunications sector, it was possible to conduct a detailed analysis of the cases used for the explanation of the results. The results measured by performance indicators found: influence of portfolio management models in the development of new products; identification, selection and prioritization of projects to optimize resources and launching in short periods of time product designs enabling to remain competitive in the market. Thus demonstrating the existence of relevant practice supported by current theory.